Growth and dressing percentage of turkeys reared of diffrent feeding regimen - Chandini Herman (Department Of Poultry Sciences,College of Veterinary and Animal Sciences, 2008)
An experiment was conducted at the Department of Poultry Science, College of Veterinary and Animal Sciences, Mannuthy to study the growth and dressing percentage of turkeys reared on different feeding regimen. Ninety six, day-old Beltsville Small White turkey poults were reared under two dietary groups with six replicates of eight birds each. The group T1 was fed with feed compounded as per NRC (1994) turkey feed specifications and T2 group was fed with BIS (1992) broiler feed. NRC diet fed group (T1) had feed change in every four week interval with CP level starting from 28% during the first four week period, gradually reduced in the subsequent 4 week periods and in the last phase of 17 to 20 weeks it was 16.5%. T2 group was fed with broiler starter diet with 23% CP and 2800 kcal ME/kg from 0 to 16 weeks and finisher diet having 20% CP and 2900 kcal ME/kg from 17 to 20 weeks of age. The turkeys were reared under standard managemental conditions up to twenty weeks of age. Body weight was recorded for individual birds at fortnightly intervals and feed balance per replicate was recorded at weekly interval. At the end of the trial, slaughter studies were conducted from two birds per replicate and blood samples were collected for serum profile studies. The mean body weight at the end of twenty weeks of age was 4338.09 and 4456.92 g respectively in T1 and T2, which was statistically comparable. Cumulative body weight gain for zero to 20 weeks was 4289.73 and 4408.51 g respectively for T1 and T2 and was statistically comparable. Cumulative feed intake for zero to 16 weeks of age was 10542.08 and 11455.00 g respectively for T1 and T2 which showed statistical difference at 5% level. The cumulative feed intake from zero to 20 weeks of age was significantly higher (P < 0.05) in T2 (15735.89 g) than T1(14310.69 g). The cumulative feed conversion ratio for zero to 16 and zero to 20 weeks showed significantly (P < 0.050) superior values for T1(3.02 and 3.34 respectively) than T2 (3.14 and 3.53 respectively). Cumulative feed intake and cumulative FCR for zero to twelve weeks were nonsignificant. The dressing percentage, eviscerated yield, ready to cook yield, and giblet yield were not influenced by the dietary regimen. The diets studied did not have any influence on the serum total protein and serum total cholesterol values in turkeys. But thigh meat cholesterol in male turkeys was significantly (P < 0.05) higher in T1 than in T2. Dietary regimen had no effect in altering the breast meat cholesterol in turkeys. Livability in both the groups was unaffected by change in diet. The results obtained from this study showed that turkeys reared for meat purpose can be economically raised by feeding them with BIS broiler feed.